Social media addiction and depression among adolescents in two Malaysian states - Sarina Binti Yusup, Khairul Azam bin Bahari, Loh Yoke Ling, Nur Nadia Binti Abd Mubin, Stephanie Ann A/P A. Victor (Tanjung Malim, 2024)
Social media addiction and depression among adolescents in two Malaysian states by Sarina Binti Yusup, Khairul Azam bin Bahari, Loh Yoke Ling, Nur Nadia Binti Abd Mubin, Stephanie Ann A/P A. Victor